Extracellular vesicles derived from physiologically loaded living myocardial slices improve the contractility of healthy living myocardial slices. (14th October 2021) - Nicastro, L; Kyriakou, A; Emanueli, C; Terracciano, C M N
Abstract: Introduction: Mechanical load is a determinant of the healthy-to-failing myocardium transition. Extracellular vesicles (EVs) found in the range of 30–200 nm contain bioactive cargoes such as DNA, miRNA and proteins, and thus are considered important mediators of the paracrine crosstalk between cells in health and disease. Living myocardial slices (LMS) are 300μm layers of myocardial tissue that allow modelling of the intercellular communication in the heart. Purpose: To assess whether secretion of EVs derived from physiological or pathological mechanically-loaded LMS regulate changes in myocardial contractility. Methods: LMS were prepared from adult male Sprague-Dawley rats' left ventricle using a vibratome. LMS were stretched uniaxially using customised stretchers at a sarcomere length of 2.2μm and 2.4μm to recapitulate a physiological (P) and an overload (O) condition, respectively. LMS were cultured for 48-hours under electromechanical stimulation in M-199 media with Earls' salts, catecholamines, dexamethasone and triiodothyronine. After culture, media was harvested and processed for exosomes isolation by size exclusion chromatography. Particle size and concentration was assessed by nanoparticle tracking analysis. To validate the different phenotypes in LMS, force-stretch relationship was assessed after 48-hours culture. EVs isolated from P and O LMS were then used to treat physiologically loaded LMS (1x107 particles/LMS) and the force-stretch relationship was assessed after 48-hours culture. Results: No significant difference in contractility was found between P and O LMS at any stretch increment (5.99±1.10 vs 2.82±0.92 mN/mm 2 max force), whilst a significant increase in the passive tension of myocardial tissue was observed at 25% (15.90±2.77 vs 4.67±0.37 mN/mm 2 ; p<0.05, ) and 30% stretch (21.92±3.60 vs 5.73±0.6 mN/mm 2 ; p<0.001) in the P LMS compared to O LMS (n=11 P, n=4 O). EVs quantification showed no significant difference between P and O conditions (1.16329E+11±4587386608 vs 1.08915E+11±7641744894 particles/ml); (n=7 P; n=3 O). However, P EVs-treated LMS showed a significant increase in contractility after 48-hours, compared to PBS-treated LMS at 25% (8.49±0.62 vs 5.34±0.9 mN/mm 2 ) and 30% stretch (9.55±0.42 vs 5.99±1.10 mN/mm 2 ; p<0.05); (n=11 PBS, n=4 P EVs, ) and O EVs-treated LMS from 15–30% stretch (9.55±0.42 vs 3.23±0.55 mN/mm 2 max force; p<0.0001); (n=4 P EVs, n=5 O EVs). Conversely, no significant differences in contractility were found between PBS-treated LMS and O EVs-treated LMS (5.99±1.10 vs 3.23±0.55 mN/mm 2 maximum force); (n=5 O EVs, n=11 PBS). Conclusions: EVs derived from physiologically loaded LMS improve the contractility of healthy LMS after 48-hours culture compared to PBS-treated LMS. Understanding how mechanical load correlates with specific loading of cargoes in EVs may reveal interesting therapeutic targets for the treatment of heart failure. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart Foundation